Partial Order in Environmental Chemistry - Bruggemann, Rainer; Carlsen, Lars (Current Computer - Aided Drug Design, 2020)
Background: The theory of partial order is a branch of Discrete Mathematics and is often seen as pretty esoteric. However, depending on a suitable definition of an order relation, partial order theory has some statistical flavor. Here we introduce the application of partial order for environmental chemistry. Objective: We showed that partial order is an instrument, which at the same time, has both data exploration - and evaluation potency. Methods: The partial order theory was applied in this study. It depends on four indicators which describe the environmental hazards of chemicals. Results: Nineteen organic chemicals were found within a monitoring study in the German river Main and were taken as an exemplary case. The results indicated that chemicals can have a high risk on the environment, however, the type of risk is different and should not conceptually merge into a single quantity. Conclusion: Partial order theory is of help to define different regulations and environmental management plans.
Keywords: descriptors of chemicals behavior